Real-life data on pasireotide in monotherapy or combined in active Cushing’s disease - Mondin, Alessandro; Ceccato, Filippo; Scaroni, Carla; Denaro, Luca; Manara, Renzo; Robertazzo, Umberto Maria; Barbot, Mattia (Frontiers in Endocrinology, 2025)
IntroductionIn the last few years, the use of medical treatment in Cushing’s disease (CD) has increased thanks to the availability of new molecules. Nevertheless, real-life data on combination treatments are still lacking.MethodsThis is a retrospective monocentric study evaluating the real-life efficacy and safety of pasireotide alone or when combined with cabergoline or metyrapone.ResultsA total of 18 patients (94% women; median age, 45 years) with active CD received pasireotide (median, 8 months), followed by a combination treatment (median, 22 months) with either cabergoline (2/9) or metyrapone (7/9) for half of the patients. Pasireotide alone significantly reduced urinary free cortisol (UFC) and late-night salivary cortisol (LNSC) (p < 0.01), achieving normal values in 59% and 38% of cases, respectively. The second cortisol-lowering agent tended to further reduce UFC (overall normalization, 67%) but had little effect on LNSC. Pasireotide led to significant hyperglycemia in 61% of cases, while the add-on drug was well-tolerated. Comorbidities were analyzed accounting for the individual cardiovascular risk and for changes in concomitant treatments. Half of the patients showed improved pressure profile. Cholesterol levels tended to decrease, and a significant weight loss was observed (>5% in 47% of cases). Add-on treatment with dose reduction of pasireotide allowed better glycemic control in one of two cases.DiscussionOur experience confirms the efficacy of pasireotide on the UFC, especially in combined regimens, but also the difficulty of restoring circadian rhythm in CD. This is the first study to report metyrapone add-on to pasireotide, but larger studies are needed to further investigate this association. Pasireotide surely worsens glucose homeostasis, but its positive effects, alone or combined, on blood pressure, lipid profile, and body weight justify its use under careful hyperglycemia management.